Development and Qualification of an Antigen Integrity Assay for a Plasmodium falciparum Malaria Transmission Blocking Vaccine Candidate, Pfs230 - Kazutoyo Miura; Thao P. Pham; Shwu-Maan Lee; Jordan Plieskatt; Ababacar Diouf; Issaka Sagara; Camila H. Coelho; Patrick E. Duffy; Yimin Wu; Carole A. Long (Vaccines, 2022)
During development of a subunit vaccine, monitoring integrity of the recombinant protein for process development and quality control is critical. Pfs230 is a leading malaria transmission blocking vaccine candidate and the first to reach a Phase 2 clinical trial. The Pfs230 protein is expressed on the surface of gametes, and plays an important role in male fertility. While the potency of Pfs230 protein can be determined by a standard membrane-feeding assay (SMFA) using antibodies from immunized subjects, the precision of a general in vivo potency study is known to be poor and is also time-consuming. Therefore, using a well-characterized Pfs230 recombinant protein and two human anti-Pfs230 monoclonal antibodies (mAbs), which have functional activity judged by SMFA, a sandwich ELISA-based in vitro potency assay, called the Antigen Integrity Assay (AIA), was developed. Multiple validation parameters of AIA were evaluated to qualify the assay following International Conference on Harmonization (ICH) Q2(R1) guidelines. The AIA is a high throughput assay and demonstrated excellent precision (3.2 and 5.4% coefficients of variance for intra- and inter-assay variability, respectively) and high sensitivity (>12% impurity in a sample can be detected). General methodologies and the approach to assay validation described herein are amenable to any subunit vaccine as long as more than two functional, non-competing mAbs are available. Thus, this study supports future subunit vaccine development.